Interaction Role Of Independent Audit Committee And Women Directors On Board Independence And Private Information-Based Trading In Malaysia - Khong, Jiunn Shyan (2020)
Private information-based trading (PIBT) or insider trading still remained as one of the crucial issues in Malaysia today despite the presence of insider trading law. Indeed, regulation on insider trading alone is not sufficient to address the PIBT issue. Among the other aspect that would help to mitigate the PIBT issue, number of independent director can be one important factor. Based on the agency theory, tradings on private information will causes agency conflict. In this regard, independent directors can actually contribute to reduce this conflict. However, there is a need to study through which channel independent directors can reinforce their monitoring over the PIBT activities. Using a sample of 811 public listed companies from the Main Board of Bursa Malaysia from year 2009 to 2017, this study investigated the effect of board independence, as well as whether statutory role of independent directors (independent audit committee) and demographic characteristics of directors (women directors) could contribute in strengthening the role of board independence in mitigating the PIBT issue. In addition to the static panel data analyses, this study also utilizes dynamic generalized method of moment estimators to resolve the endogeneity problem and persistent PIBT issue. The findings indicated that independent directors are statistically significant in mitigating PIBT. Besides, independent audit committee and women directors also having negative and significant interaction effects. This suggests that both factors could strengthen the effect of board independence in mitigating PIBT.